Affordable echelle spectroscopy of the eccentric HAT‐P‐2, WASP‐14, and XO‐3 planetary systems with a sub‐meter‐class telescope. Issue 1 (17th February 2017) - Garai, Z.; Pribulla, T.; Hambálek, Ľ.; Kundra, E.; Vaňko, M.; Raetz, S.; Seeliger, M.; Marka, C.; Gilbert, H.
Abstract : Background: A new off‐the‐shelf, low‐cost echelle spectrograph was installed recently on the 0.6‐m telescope at the Stará Lesná Observatory (Slovakia). In this paper, we describe in detail the radial velocity (RV) analysis of the first three transiting planetary systems, namely HAT‐P‐2, WASP‐14, and XO‐3, observed with this instrument. Materials and Methods: First, we reduced and analyzed our RV observations. Subsequently, we compared our data with previously published RV data. We were curious about the precision of our measurements in comparison to that of the RV data achieved with echelle spectrographs of other sub‐meter‐, meter‐ and 2‐m‐class telescopes. Another question was the applicability of our RV data for modeling orbital parameters. For this purpose, the previously published data were analyzed in the same way as our RV data in order to determine and compare the parameters. Finally, we combined and analyzed all used RV data per object. Results: The accuracy of our data is well comparable with the average RV scatter achieved with other sub‐meter and meter‐class telescopes. In comparison with 2‐m‐class telescopes, our instrumentation gives an RV scatter of about one order greater. On the other hand, our fit results show that RV data obtained with our instrumentation can be used to determine orbital parameters of these objects. Conclusion: Based on our results, we can conclude that the spectrograph is a useful instrument for the study of objects with a relatively small RV amplitude. Resulting values are sufficient for exoplanet RV detections and spectroscopic follow‐up measurements of massive exoplanets on close‐in orbits.